Comparative study of Diffserv schedulers - Priority Queue & Weighted Round Robin - Nor Fairuz Binti Osman (2023)
This project is to carry out a comparative study of Diffserv schedulers. In Diffserv, there are four types of schedulers that usually are used to schedule the packet in the network; Weighted Round Robin, Weighted Interleaved Round Robin, Round Robin and Priority Queue. This comparative study was conducted based on Priority Queue and Weighted Round Robin and the parameters that being studied are queue size and queue loss. A simulation study was conducted using two scheduling techniques. By looking at these parameters, the effectiveness of Quality of Service (QoS) provided by Diffserv scheduling technique are studied.